European Respiratory Society International Congress 2018: highlights from Assembly 2 on respiratory intensive care. Issue 1 (4th March 2019) - Fisser, Christoph; Spoletini, Giulia; Soe, Aung Kyaw; Livesey, Alana; Schreiber, Annia; Swingwood, Ema; Bos, Lieuwe D.; Dreher, Michael; Schultz, Marcus J.; Heunks, Leo; Scala, Raffaele
The respiratory intensive care Assembly of the European Respiratory Society is proud to present a summary of several important sessions held at the International Congress in Paris in 2018. For the highly esteemed reader who may have missed the Congress, a concise review was written on three topics: the state-of-the-art session on respiratory critical care, hot topics in weaning and the best abstracts in noninvasive ventilation. The respiratory intensive care Assembly of the European Respiratory Society is proud to present a summary of several important sessions from the 2018 #ERSCongress in Paris http://ow.ly/6Du830nFESK